La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter presents a profile of the socio-demographic characteristics and the health of Francophone seniors (aged 65 and above) living in minority language communities, and identifies the issues and the needs of this population. In the first section of the chapter, we discuss the minority context and its potential impact on the aging of the population, the social position of seniors, their health, and their access to services. The second section establishes the socio-sanitary profile of Francophone seniors in three large Canadian regions (Atlantic Canada, Ontario, and the West), based on data from the Canadian Community Health Survey—Annual Component (CCHS, combined cycles, 2003–2012). Finally, we discuss two issues that are, we believe, fundamental for this minority population: health literacy—the ability to adequately communicate in and navigate through the health system—and the active offer of services, which is a measure of equity and quality of care for people living in an official language minority community. Key Words: Francophone seniors, linguistic minorities, socio-sanitary portrait, Canada, Canadian Community Health Survey (CCHS).

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Besoins et services en français en matière de sexopérinatalité chez les couples parentaux franco-ontariens - de Pierrepont, Catherine; Polomeno, Viola; Bouchard, Louise; Reissing, Elke (Minorités linguistiques et société, 2017)
Cet article dévoile un portrait des besoins et des services en français en matière de sexopérinatalité perçus par 67 couples parentaux francophones en situation linguistique minoritaire d’Ottawa et de l’Est de l’Ontario. Les couples ont des besoins d’informations et de soutien ; pour eux, il est important d’aborder la sexualité pendant la période périnatale. Toutefois, le sujet est peu discuté avec les professionnels de la santé, et très peu de services sexopérinataux en français sont offerts, même s’ils sont souhaités par ces couples. Les discussions sur la sexualité qui se déroulent majoritairement en anglais constituent un obstacle supplémentaire pour une majorité des couples. Mots-clés : sexualité périnatale, couples parentaux, périnatalité, francophones en situation linguistique minoritaire, services de santé en français

Santé dans le Nord - Rapport sur la géographie et la santé de la population des deux régions du Nord de l'Ontario - Qualité des services de santé Ontario (2017)
Ce rapport présente un état de la santé des populations vivant dans le Nord de l’Ontario, incluant une courte section consacrée à la santé des francophones, ainsi que des recommandations concernant les services destinés à cette population.

Cognitive health initiative for Francophone seniors in the GTA: Options fo Service Models - Reflet Salvéo; Entité 4 (2017)
Like the general population, the Francophone population is aging and at a faster rate than the population as a whole. While the median age for the Ontario population is 40.1 years, it is 44 for Francophones, and the largest age categories among Francophones are 45-54 and 65 and over: almost one out of five Francophones is included in these age groups. Although the population of the Central Region, including the Greater Toronto Area (GTA), is somewhat younger, the median age of Francophones is still higher than that of the Central Region population as a whole (41.1 vs 39.4) 4. Yet services for people with cognitive disorders and their families and caregivers are fragmented and do not necessarily meet their needs or the demand for service. The situation for those seeking services in French is even worse. Language and culture are key factors in providing quality, safe care. Language barriers constitute a major obstacle for people with dementia and their caregivers and families. Many Francophones lose their second language and revert to their mother tongue as they age, particularly when they are under stress; this is especially true for people coping with dementia. It is essential that Francophones with dementia and their caregivers have equitable access to a continuum of culturally sensitive quality care in French at every stage of the dementia journey. To meet the growing needs of the GTA’s aging Francophone population, the two French language health planning entities, Reflet Salvéo and Entité 4, have partnered on a feasibility study on cognitive health together with the five GTA LHINs (Central West, Mississauga Halton, Toronto Central, Central and Central East), Centres d’Accueil Héritage (CAH) and the Glendon Centre for Cognitive Health. The purpose of the study is to develop options for service models for memory services, including a memory clinic, focussing on very early detection and intervention for mild cognitive impairment but also addressing the need for referrals and supports for those farther along on the dementia journey, and their caregivers. The initiative will build on work previously done on memory centre services in French and on initiatives developed and implemented in the five GTA LHINs. The models proposed will align with LHIN and provincial strategic priorities for dementia and services for seniors and focus on helping people experiencing cognitive decline to remain active participants in their communities for as long as possible. Methodology The first step was a brief analysis of a previous literature review along with a number of studies, reports and plans dealing with the impact of dementia and current service models as well as provincial and LHIN strategic priorities and initiatives for the next several years. Research was also conducted into the availability of services for people with dementia and their caregivers both overall and in French. The next steps involved gaining an overview of existing models and opportunities. As a second stage, interviews were held with LHIN representatives to develop a picture of LHIN priorities and approaches to dementia services in a context of profound system transformation affecting home and community care, primary care and putting the focus on patients, including seniors. Subsequently, following development of a discussion guide, interviews were conducted with health service providers, both those serving the population as a whole and those identified to provide services in French. Another important step was seeking the voice of the Francophone community through a mixture of focus groups and online surveys. Once options are developed, we will go back to providers and the community to seek their input and validate our recommendations. Work on the project as a whole was overseen and supported by a steering committee that included representatives of the two French language health planning entities and the five GTA LHINs as well as the Glendon Centre for Cognitive Health and Centres d’Accueil Héritage (CAH).

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)
pages: 106